Tea tree essential oil and its impact on blue mold, volatile compounds, and postharvest quality of ‘Fuji’ apples: A study of laboratory-extracted and commercial essential oils - da Silva J.C.* (2024)
© 2024 Elsevier LtdThis study evaluated the effects of tea tree essential oil (TTO) on blue mold severity, volatile compound profiles, and postharvest quality of ‘Fuji’ apples during cold storage. Two experiments were conducted using laboratory-extracted TTO from Brazil and commercial TTO from Australia, applied by vaporization at various concentrations. Both types of TTO affected major volatile compounds, including terpinen-4-ol, γ-terpinene, and α-terpinene. The laboratory-extracted TTO had higher of 1,8-cineole, while commercial TTO had more p-cymene. TTO reduced blue mold severity up to 115 μL L−1 (laboratory) and 99 μL L−1 (commercial). Ethylene production decreased with laboratory-extracted TTO up to 64 μL L−1, while commercial TTO decreased ethylene production. Laboratory TTO increased the respiratory up to 41 μL L−1 before declining, whereas commercial TTO continuously decreased the respiratory. Higher concentrations of laboratory TTO decreased flesh firmness and lightness.TTO types altered the apples' volatile profiles, reducing ‘Fuji’ apple aromas.